Supply Chain Recent Advances and New Perspectives in the Industry 4.0 Era - Bányai, Tamás; Bányai, Ágota; Kaczmar, Ireneusz (IntechOpen, 2022)
The Fourth Industrial Revolution has led to revolutionary changes in production and service processes. This book explains and examines the impact of Industry 4.0 technologies on supply chain solutions. It discusses the concept, design, and implementation of supply chain solutions using Industry 4.0 technologies. Chapters address such topics as supply webs, open innovation practices, lean manufacturing, the Internet of Things, green supply chain solutions, and much more.